2013
DOI: 10.1111/hae.12240
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in haemophilia: a single institutional cross‐sectional study

Abstract: Introduction Haemophilia has been associated with low bone mineral density (BMD). However, prior clinical studies of this population have neither clearly elucidated risk factors for development of low BMD nor identified who may warrant screening for osteoporosis. Aim To evaluate the relationship between BMD and hemophilic arthropathy and other demographic and clinical variables. Methods We undertook a cross-section study of BMD in adult men with haemophilia. Measures of predictor variables were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 34 publications
2
73
3
Order By: Relevance
“…In a Mediterranean population of 104 haemophilic adults, it was found that low BMD (Z‐score ≤−2 or T‐score ≤−1) was present in 32%, 43% and 20% of patients with severe, moderate and mild disease, respectively . Another study showed that in 61 patients under 50 years, there were 29%, 20% and 8% of patients with low BMD, in severe, moderate and mild cases, respectively, while the percentages of reduced bone mass in the three severity classes in 26 patients over the age of 50 were 44%, 25% and 39%, respectively . In the normal male population, the prevalence of osteoporosis is 3% between 50 and 59 years and 10% in the men over 80 .…”
Section: Discussionmentioning
confidence: 49%
“…In a Mediterranean population of 104 haemophilic adults, it was found that low BMD (Z‐score ≤−2 or T‐score ≤−1) was present in 32%, 43% and 20% of patients with severe, moderate and mild disease, respectively . Another study showed that in 61 patients under 50 years, there were 29%, 20% and 8% of patients with low BMD, in severe, moderate and mild cases, respectively, while the percentages of reduced bone mass in the three severity classes in 26 patients over the age of 50 were 44%, 25% and 39%, respectively . In the normal male population, the prevalence of osteoporosis is 3% between 50 and 59 years and 10% in the men over 80 .…”
Section: Discussionmentioning
confidence: 49%
“…A significant negative correlation was found between DEXA z‐score and HJHS in children with severe haemophilia A ( R = −.315) and ( P = .026). Similarly, Kempton et al reported that HJHS was significantly correlated to decreased BMD, accounting for 23% of the variation seen in BMD in adults with haemophilia. For each one‐point increase in the radiographic HJHS, there was a decrease in BMD of 0.006 g/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…After approval by the Emory University Institutional Review Board, patients with haemophilia A or B aged ≥ 25 years were recruited from the Emory/Children’s Health Care of Atlanta (CHOA) Comprehensive Haemophilia Treatment Center (HTC) to participate in a study of bone density ([20]. Originally, 163 patients were eligible for inclusion based on age and receipt of treatment at the Emory/CHOA HTC.…”
Section: Methodsmentioning
confidence: 99%